Symbiotic and antibiotic interactions between gut commensal microbiota and host immune system - Malys, Mantas Kazimieras; Campbell, Laura; Malys, Naglis (Lithuanian University of Health Sciences, 2015)
The human gut commensal microbiota forms a complex population of microorganisms that survive by maintaining a symbiotic relationship with the host. Amongst the metabolic benefits it brings, formation of adaptive immune system and maintenance of its homeostasis are functions that play an important role. This review discusses the integral elements of commensal microbiota that stimulate responses of different parts of the immune system and lead to health or disease. It aims to establish conditions and factors that contribute to gut commensal microbiota's transformation from symbiotic to antibiotic relationship with human. We suggest that the host-microbiota relationship has been evolved to benefit both parties and any changes that may lead to disease, are not due to unfriendly properties of the gut microbiota but due to host genetics or environmental changes such as diet or infection.